Removal of Arsenic from Solution by Water Hyacinth (Eichhornia crassipes (Mart) Solms). - Low, K. S.; Lee, C. K. (1990)
The potential of water hyacinth (Eichhornia crassipes (Mart) Solms) as a bioacummulatorl bioindicator of arsenic in dilute solution was investigated. Results show that in the absence of a high level of phosphate, it can remove arsenic effectively. However, in high phosphate concentration, arsenic uptake was inhibited. A arsenic could also be leached out from the plant. Hence caution must be exercised in interpreting the arsenic status of the aquatic environment as seen through water hyarcinth.